The Role of Boundary Spanning Strategy in Mediating the Improvement of Organizational Performance: A Study on the Indonesian Ministry of Health Hospital - Paryanto, Paryanto; Arafah, Willy; Anggiani, Sarfilianty (Research Collaboration Community (RCC), 2025)
Purpose - This study aims to analyze the role of Boundary Spanning Strategy in mediating the influence of Organizational Culture, Strategic Leadership, and Job Satisfaction on Organizational Performance within the context of a study conducted at Ministry of Health hospitals in Indonesia. These hospitals are characterized by resource-intensive operations, substantial capital, advanced technology, detailed procedures, and complex challenges. Additionally, strict regulations, silo culture, and bureaucratic complexity often hinder innovation and managerial effectiveness. Methodology - This study adopts a quantitative approach using a non-random purposive sampling technique with a cross-sectional or one-shot design. Data were collected through an online questionnaire distributed to top- and middle-level managers across 37 Ministry of Health hospitals throughout Indonesia. A total of 320 responses were collected and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 3 software. Findings - The results indicate that Boundary Spanning Strategy fully mediates the influence of Strategic Leadership on Organizational Performance and partially mediates the influence of Organizational Culture on Organizational Performance. Meanwhile, although Job Satisfaction has a direct influence on Organizational Performance, its indirect effect through Boundary Spanning Strategy is not significant, indicating the absence of mediation. Implications - The theoretical implication of this research is to extend the understanding of organizational theories, particularly Resource-Based View and Organizational Behavior Theory, by emphasizing the critical role of boundary-spanning strategies in enhancing organizational performance. Practically, the findings offer guidance for hospital managers to strengthen boundary-spanning competencies, prevent silo culture, and foster cross-unit collaboration within the organization. Furthermore, this study underscores the importance of regulatory support to encourage boundary-spanning behaviors in the healthcare sector. Research Limitations - The limitations of this study include the use of a single quantitative approach and a cross-sectional design, which restrict the understanding of the dynamic relationships between variables over time. Therefore, future research is recommended to employ a mixed-methods approach with a longitudinal design to gain a more comprehensive insight into the studied phenomenon.